Too Connected to Fail: The Regulation of Systemic Risk within Australia's Superannuation System. Issue 1 (11th December 2015) - Donald, Scott; Bateman, Hazel; Buckley, Ross; Liu, Kevin; Nicholls, Rob
Abstract: The funds, entities, and regulators involved in the Australian superannuation industry together comprise a system that is complex and dynamic. The differentiation between roles and the distribution of responsibility amongst entities provides the system with a measure of resilience against the local failure of any one of the entities. However, the interconnections that bind and constitute the system also have the potential to transmit risks within the system, creating the potential for the impact of local failures to amplify through propagation, or in other ways to pose risks to the system as a whole. This article uses a new data set on 200 of Australia's largest superannuation funds to map and assess those links and to identify the challenges those links pose to the scheme of prudential regulation applied to the superannuation system in Australia. It finds that the function of the entity and the legal form of the linkages, both of which are more variegated than typically occurs in banking sector transactions, crucially influences whether, and to what extent, various types of failures might be transmitted across the system. It also finds that we may be materially under-estimating the possibility that local failures in the superannuation system, which are a near certainty given the current regulatory risk appetite, will have a systemic impact. The findings have broad application across pension and institutional investment markets worldwide.